Liposomes and lipid disks traverse the BBB and BBTB as intact forms as revealed by two-step Förster resonance energy transfer imaging - Tongcheng Dai; Kuan Jiang; Weiyue Lu (Elsevier, 2018)
The blood-brain barrier (BBB) and the blood-brain tumor barrier (BBTB) prevent drug and nano-drug delivery systems from entering the brain. However, ligand-mediated nano-drug delivery systems have significantly enhanced the therapeutic treatment of glioma. In this study we investigated the mechanism especially the integrity of liposomes and lipid disks while traversing the BBB and BBTB both in vitro and in vivo. Fluorophores (DiO, DiI and DiD) were loaded into liposomes and lipid disks to form Förster resonance energy transfer (FRET) nano-drug delivery systems. Using brain capillary endothelial cells as a BBB model, we show that liposomes and disks are present in the cytoplasm as their intact forms and traverse the BBB with a ratio of 0.68‰ and 1.67‰, respectively. Using human umbilical vein endothelial cells as BBTB model, liposomes and disks remained intact and traversed the BBTB with a ratio of 2.31‰ and 8.32‰ at 3 h. Ex vivo imaging and immunohistochemical results revealed that liposomes and disks could traverse the BBB and BBTB in vivo as intact forms. In conclusion, these observations explain in part the mechanism by which nano-drug delivery systems increase the therapeutic treatment of glioma. KEY WORDS: Liposomes, Disks, Intact form, BBB, BBTB, FRET